Effects of Mannanase Supplementation and Citric Acid on the Growth Performance of Broilers - Maria Patricia Arellano; Listya Purnamasari; Joseph dela Cruz (Buletin Peternakan, 2022)
The study was conducted to evaluate the effects of citric acid and mannanase feed supplementation on the growth performance of broiler chickens. Three hundred twenty day-old unsexed Cobb broiler chicks from a commercial hatchery plant were used in the study. The chicks were randomly assigned to four treatment groups following a completely randomized design. The following treatment groups were used: T1: Control, T2: 3% (w/w) Citric Acid supplementation, T3: 80 ppm β-Mannanase supplementation, and T4: 3% (w/w) Citric Acid and 80 ppm β-Mannanase supplementation. The supplementation of citric acid and mannanase significantly improves the growth performance of broiler chickens. Body weight and body weight gain were significantly higher (P<0.05) in the citric acid and β-mannanase combination group compared to all the treatment groups. The evaluation of feed intake revealed that T3 and T4 had significantly lower (P<0.05) feed intake than the other groups. The combination of citric acid and β-Mannanase also resulted in a significantly more efficient (P<0.05) feed conversion ratio. No mortality was observed during the experiment. It may be concluded that the supplementation of citric acid and β- mannanase resulted in a better performance in broilers.